2010
DOI: 10.1093/nar/gkq999
|View full text |Cite
|
Sign up to set email alerts
|

REDfly v3.0: toward a comprehensive database of transcriptional regulatory elements in Drosophila

Abstract: The REDfly database of Drosophila transcriptional cis-regulatory elements provides the broadest and most comprehensive available resource for experimentally validated cis-regulatory modules and transcription factor binding sites among the metazoa. The third major release of the database extends the utility of REDfly as a powerful tool for both computational and experimental studies of transcription regulation. REDfly v3.0 includes the introduction of new data classes to expand the types of regulatory elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
220
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(221 citation statements)
references
References 10 publications
1
220
0
Order By: Relevance
“…Given this, we next investigated the direct relationship between eRNA and enhancer activity during Drosophila embryogenesis, making use of the thousands of characterized developmental enhancers whose spatial and temporal activity has been assessed in vivo in transgenic embryos (Gallo et al 2011;Bonn et al 2012a;Kvon et al 2014). Both PRO-cap and CAGE signals were used as two independent measures of eRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this, we next investigated the direct relationship between eRNA and enhancer activity during Drosophila embryogenesis, making use of the thousands of characterized developmental enhancers whose spatial and temporal activity has been assessed in vivo in transgenic embryos (Gallo et al 2011;Bonn et al 2012a;Kvon et al 2014). Both PRO-cap and CAGE signals were used as two independent measures of eRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…We first ranked enhancers-both in vivo characterized (Gallo et al 2011;Bonn et al 2012a;Kvon et al 2014) and predicted (Zinzen et al 2009)-by their levels of eRNA based on their nascent PRO-cap signal ( Fig. 3A; Supplemental Table S8).…”
Section: Highly Transcribed Developmental Enhancers Have Weak Promotementioning
confidence: 99%
See 1 more Smart Citation
“…We then selected an additional 14 enhancers from the REDfly database of known Drosophila cis regulatory elements (Gallo et al 2011) (Table 1). We focused on enhancers that are active in stereotyped patterns across the developing ommatidial clusters of the third instar larval eye disc, reasoning that this tissue is generally permissive to transvection based on prior analyses (Leiserson et al 1994;Wu and Howe 1995;Bateman et al 2012a).…”
Section: Resultsmentioning
confidence: 99%
“…To generate piB-LTL-lacZ derivatives carrying different enhancers, potential target enhancers were identified using the REDFly database (Gallo et al 2011), and primers for amplifying enhancer sequences were either identified from a previous publication (Aerts et al 2010) or designed using Primer3 software (Untergasser et al 2012). Enhancer sequences were amplified via PCR from Drosophila genomic DNA and cloned into either pcr2.1 using a TOPO-TA cloning kit (Invitrogen) or pSC-A using a Strataclone PCR cloning kit (Agilent Technologies).…”
Section: Plasmid Construction and Transgenicsmentioning
confidence: 99%